Efektivitas Program Asuransi Kehilangan Pekerjaan Sistem Jaminan Sosial di Indonesia, Malaysia dan Jepang - Fitraeva Pane, Yos; Agusmidah, Agusmidah; Affila, Affila; Sukarja, Detania (Universitas Jambi, Fakultas Hukum, 2024)
Social security, according to the ILO, is a protection system to protect people from social and economic risks. In Indonesia, the formal worker social security system does not yet cover the entire community, especially in the informal sector. For this reason, Indonesia introduced the Job Loss Guarantee (JKP) program to protect workers who lose their jobs, with cash benefits, labor market information, and training. This program was inspired by countries such as Malaysia and Japan that had already implemented it. Indonesia adopted ILO standards in Conventions 102 and 168 to improve social protection, including unemployment benefits and employment opportunities. The conclusion from the discussion of the JKP program in Indonesia, Malaysia, and Japan is that the JKP system in Indonesia still has several shortcomings, such as participation requirements in other social security programs that hinder registered workers, small cash benefits, and complicated procedures. Job training benefits are also not optimal. In Malaysia, the JKP program effectively protects workers in the formal and informal sectors with a benefit duration of between 3 to 6 months, while Japan provides varying benefits, with a duration of between 3 to 12 months. To increase the effectiveness of the Indonesian JKP, it is necessary to simplify the process and improve the administrative system so that more workers can access its benefits.